TEACHING WRITING OF NARRATIVE TEXT THROUGH DIGITAL COMIC - Fenti Susilawati (Journal of English and Education, 2017)
This research was aimed to investigate the use of digital comic in helping senior high school students to write narrative text and to find out the students’ perception on the use of digital comic in teaching writing of narrative text. This research employed a quantitative method with a true experimental design. The sample of this research was the 10th-grade students at one senior high school in Garut. There were 71 students involved in this research; 36 of them belonged to experimental group and the rest were belonged to control group. Therefore, writing test and questionnaire were implemented as the research instrument in order to collect the data. Writing test of this research was implemented twice; first as a pretest and second as a posttest. In addition, Sangkuriang and Timun Mas were chosen as the title of digital comic used in this research. The result of this research indicated that the use of digital comic as teaching media can improve students’ ability in writing narrative text. The result also revealed that the use of digital comic in teaching writing of narrative text has more advantages rather than the disadvantages. From this research, teachers are recommended to use digital comic in teaching writing of narrative text.